Investing Iraq's oil under a changing economic system - a comparative economic, jurisprudential and legal study - Dr. Rand Fateikhan Atallah Al-Zaidi.,; prof. Adnan Ibrahim Abdul Jumaily, (The college of law and political science journal, 2023)
.